Characterization and comparison of the fecal bacterial microbiota in Red Back Pine Root Snake (Oligodon formosanus) and Chinese Slug-Eating Snake (Pareas chinensis) - Cong, Xiao; Liu, Xiangnan; Zhou, Dan; Xu, Yunfeng; Liu, Jinru; Tong, Fei (Frontiers in Microbiology, 2025)
IntroductionThe gastrointestinal tracts and oral cavities of animals harbor complex microbial communities that assist hosts in nutrient absorption and immune responses, thereby influencing behavior, development, reproduction, and overall health.MethodsWe utilized metagenomic sequencing technology to conduct a detailed analysis of the fecal bacterial communities of six Red Back Pine Root Snakes (Oligodon formosanus, XT) and three Chinese Slug-Eating Snakes (Pareas chinensis, Z) individuals. The microbial composition was assessed through taxonomic profiling, alpha diversity analysis, and functional annotation using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database.ResultsThe results indicated that Proteobacteria, Bacteroidetes, Firmicutes, Verrucomicrobia, Actinobacteria, and Fusobacteria were the dominant phyla in XT samples, while Z samples additionally contained Patescibacteria. Alpha diversity analysis revealed significant differences in species abundance at the family level, with Z samples exhibiting higher microbial richness than XT. Furthermore, KEGG analysis showed that XT had higher functional gene abundance in pathways related to transcription, translation, environmental adaptation, membrane transport, cellular communities (prokaryotes), motility, and replication/repair compared to Z.DiscussionThis study provides a comparative analysis of their gut microbiomes, offering valuable insights for future research on zoonotic diseases, host-microbe interactions, and ecological, evolutionary, behavioral, and seasonal influences on snake microbiota. These findings contribute to a broader understanding of microbial ecology in reptiles and its implications for conservation and disease dynamics.